Blockchain technology in tourism industry: a bibliometric analysis - Du, Yiqun; Mohamed, Rosmah; Yee, Choy Leong (Penerbit Universiti Islam Selangor, 2024)
The integration of Industry 4.0 (I4.0) technologies has significantly transformed the tourism industry. Additionally, the COVID-19 pandemic has accelerated the adoption of I4.0 technologies in this sector. However, there is limited evidence on how specific I4.0 technologies, such as blockchain, support the tourism industry, particularly in the post- pandemic era. This review seeks to provide insights into emerging research trends that incorporate blockchain technology into the tourism sector. To achieve this, a systematic literature network analysis (SLNA) was conducted, combining a systematic literature review (SLR) with bibliometric analysis. The analysis was based on a corpus of 163 studies published from 2017 to 2024, sourced from the Scopus database, and was carried out using the Biblioshiny tool in R-studio. The findings indicate that blockchain technology has gained popularity in recent years, with most research focusing on developed economies, while there is a notable gap in studies from emerging and developing economies. Tourism practitioners should consider the results of this study from multiple perspectives to enhance their current and future operations and strategies. This study introduces several novel areas, particularly concerning methodology and research context. The innovative SLNA approach was used to review blockchain applications in the tourism industry, though the study was limited to this sector. Future research could explore related topics, such as cryptography, ecosystems, and technology adoption, which are still developing in this and other fields.